HAK KEKAYAAN INTELEKTUAL DI BIDANG MEREK SEBAGAI JAMINAN TAMBAHAN PADA PERBANKAN - Miftakhur Rokhman Habibi; Rohmatul Lailatus Saidah (JURNAL PURNAMA BERAZAM, 2020)
Intellectual property rights are rights that stem from thouht or idea and that emanate fromhuman science or technology. Intellectual property is an intangible object. So too with the brand that belongs to the one in intellectual property rights. The brand is not only symbol or a mark on only goods or services, but it can also be used as securyty object if it has an economic nila. Althought there are still no laws that directly govern them but the brand is worthy of additional security. As done by BNI Bank that can make brands as addtitional collateral as long as they meet he conditions that have been made. that way they can be made collateral collatelar in accordance with the valid bail laws.